Distribution of Levels of Suitability of Land Characteristics and Growing Degree Days (GDD) for Corn (Zea mays L.) in West Sumatra - Yanti, Delvi; Sari, Elsa Novita; Safitri, Imelda; Rusnam, Rusnam (Journal of Tropical Agricultural Engineering and Biosystems - Jurnal Keteknikan Pertanian Tropis dan Biosistem, 2024)
The decline in corn production is influenced by several factors, one of which is the suitability of land characteristics. This research analyses land characteristics' suitability and GDD for West Sumatra Province corn crops. The suitability of land characteristics is studied by combining the suitability of land characteristics with the GDD value in the area. The suitability of land characteristics is determined by matching plant growth requirements and land characteristics. The parameters used to determine the suitability of land characteristics are land use, slope, soil pH, soil texture and rainfall. GDD suitability by matching the accumulated daily temperature data during one growing season to the optimal GDD value for corn plant growth. This research created 12 planting time scenarios, and the analysis was carried out based on Regency/city administrative areas in the West Sumatra region. The analysis results obtained a suitable land area based on land characteristics and GDD values, namely an area of 1,206,079.48 ha with a planting season of December-March. Areas in West Sumatra Province with great potential for corn crop development are Lima Puluh Kota Regency, Pasaman Regency, Sijunjung Regency, South Solok Regency, and Tanah Datar Regency.